INTEGRATION OF LANGUAGE SKILLS IN ESL/EFL LEARNING - Sulviana, Sulviana; Litta, Lista (Cakrawala Bahasa, 2025)
This research examines the approach of integrating language skills (listening, speaking, reading, and writing) in the context of learning English as a Second Language (ESL) or English as a Foreign Language (EFL). The integration of language skills has proven more effective than teaching skills separately as it reflects real-world language use. This study discusses practical strategies for integrating language skills, with a particular focus on the integration of listening-writing and reading-writing skills. Research findings indicate that the integrated approach enhances students' understanding of language structure, accelerates literacy development, and prepares students for effective communication in various contexts.